Genomic Insights Into the Population History and Biological Adaptation of Southwestern Chinese Hmong–Mien People - Liu, Yan; Xie, Jie; Wang, Mengge; Liu, Changhui; Zhu, Jingrong; Zou, Xing; Li, Wenshan; Wang, Lin; Leng, Cuo; Xu, Quyi; Yeh, Hui-Yuan; Wang, Chuan-Chao; et al. (Frontiers in Genetics, 2022)
Hmong-Mien-speaking (HM) populations, widely distributed in South China, North of Thailand, Laos and Vietnam, have experienced different settlement environments, dietary habits and pathogen exposure. However, their specific biological adaptation remained largely uncharacterized, which is important in the population evolutionary genetics and Trans-Omics for regional Precision Medicine. Besides, the origin and genetic diversity of HM people and their phylogenetic relationship with surrounding modern and ancient populations are also unknown. Here, we reported genome-wide SNPs in 52 representative Miao people and combined them with 144 HM people from 13 geographically representative populations to characterize the full genetic admixture and adaptive landscape of HM speakers. We found that obvious genetic substructures existed in geographically different HM populations, one localized in the HM clines and others possessed affinity with Han Chinese. We also identified one new ancestral lineage specifically existed in HM people, which spatially distributed from Sichuan and Guizhou in the North to Thailand in the South. The sharing patterns of the newly-identified homogeneous ancestry component combined the estimated admixture times via the decay of Linkage Disequilibrium and haplotype sharing in GLOBETROTTER suggested that the modern HM-speaking populations originated from Southwest China and migrated southward recently, which is consistent with the reconstructed phenomena of linguistic and archeological documents. Additionally, we identified specific adaptive signatures associated with several important human nervous system biological functions. Our pilot work emphasized the importance of anthropologically-informed sampling and deeply genetic structure reconstruction via whole-genome sequencing in the next step in the deep Chinese population genomic diversity project (CPGDP), especially in the regions with rich ethnolinguistic diversity.